Forbidden : receiving Pope Francis's condemnation of nuclear weapons - Christiansen, Drew; Sargent, Carole (Georgetown University Press, 2023)
"In 2017 the Holy See became the first state to sign and ratify the Treaty on the Prohibition of Nuclear Weapons. In November of that year the Vatican invited participants to a symposium on a World Free from Nuclear Weapons. At the conclusion of that conference, Cardinal Silvano Tomasi requested that two books be published. One would compile the papers delivered at the conference. GU Press published it as A World without Nuclear Weapons: The Vatican Conference on Disarmament in August 2020, timed to commemorate the 75th solemn anniversaries of Hiroshima and Nagasaki. For the second volume, he requested a collection of essays of pastoral and moral guidance on the condemnation, designed for teachers and counselors of ethics, other pastoral workers, and--the ultimate audience--military professionals, diplomats, and defense experts charged with supervision of nuclear weapons. Forbidden is that book. It is the collective effort of experts in many fields, especially moral theologians, defense analysts, and scholars of conflict transformation. Together these experts explain how, with Pope Francis' leadership, Church teaching on nuclear weapons has evolved from a carefully calibrated acceptance of deterrence to a blanket condemnation of both the weapons and the defense systems based on them. This book presents a necessary background of nuclear condemnation in Catholic just-war analysis. It also engages emerging approaches of moral analysis such as moral ecology and pastoral accompaniment, while interweaving the essential witness of survivors of nuclear attacks and test explosions. The contributors grapple with new thinking among American policymakers, led by the 60th US Secretary of State, the late George Shultz. In the interest of making Pope Francis' teaching "church-wide and parish-deep," this book takes up questions of conscience formation and pastoral accompaniment, as well as public education and the mobilization of lay Catholic movements. Of note are chapters dedicated to those with special responsibility for nuclear armaments: the missile personnel ("nuclear stewards"), officers in the chain of command, weapons scientists, legislators, military industrialists and citizens in nuclear-armed states"--